2022
DOI: 10.7717/peerj.13708
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of the enhancer of zeste homolog 1 transcriptional factor predicts poor prognosis of triple-negative breast cancer patients

Abstract: Background Triple-negative breast cancer (TNBC) is the most malignant subtype of breast cancer and lacks effective biomarkers. This study seeks to unravel the expression status and the prospective transcriptional mechanisms of EZH1/EZH2 in TNBC tissue samples. Moreover, another objective of this study is to reveal the prognostic molecular signatures for risk stratification in TNBC patients. Methods To determine the expression status of EZH1/EZH2 in TNBC tissue samples, microarray analysis and immunohistochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…EZH1 is deemed to be relevant to the occurrence and development of tumors. Previous studies showed that in triple-negative breast cancer, the expression levels of EZH1 protein and mRNA show a down regulation [15], while EZH1 overexpression significantly eliminates the function of TRIM21 protein to induce apoptosis of cancer cells in gastric cancer [16]. Therefore, the role of EZH1 in different tumors is complex.…”
Section: Discussionmentioning
confidence: 99%
“…EZH1 is deemed to be relevant to the occurrence and development of tumors. Previous studies showed that in triple-negative breast cancer, the expression levels of EZH1 protein and mRNA show a down regulation [15], while EZH1 overexpression significantly eliminates the function of TRIM21 protein to induce apoptosis of cancer cells in gastric cancer [16]. Therefore, the role of EZH1 in different tumors is complex.…”
Section: Discussionmentioning
confidence: 99%